The importance of the dialogue between theology and science from an anthropological analysis perspective - Petrov, George Daniel (Technium Social Sciences Journal, 2021)
The anthropological chapter defines itself as the most important research that mankind can undertake, as it brings to the foreground aspects that give meaning to the entire universe. The dialogue between science and theology is imperatively necessary in defining man, as only through co-working can man be correctly defined in his dichotomy, thus pointing out elements of evolution as much as elements related to the spiritual side of man, side that takes him out of „contingency” and positions him in the love of God.